2014
DOI: 10.1039/c4ra08362h
|View full text |Cite
|
Sign up to set email alerts
|

Dispersible composites of exfoliated graphite and polyaniline with improved electrochemical behaviour for solid-state chemical sensor applications

Abstract: The PANI–graphene/graphite composites show improved pH stability and electrochemical behaviour in aqueous electrolyte solutions at pH ≤ 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 67 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…The polar β-phase bands of P(VDF-TrFE) appear distinctly at $ 846, $ 1285 and $ 1400 cm À 1 . The $ 1285 and $ 846 cm À 1 bands belong to the CF 2 symmetric stretching and the 1400 cm À 1 band is assigned to the CH 2 wagging vibration [33,34]. The position of the absorption bands does not exhibit noticeable change in graphene-P(VDFTrFE) film.…”
Section: Resultsmentioning
confidence: 98%
“…The polar β-phase bands of P(VDF-TrFE) appear distinctly at $ 846, $ 1285 and $ 1400 cm À 1 . The $ 1285 and $ 846 cm À 1 bands belong to the CF 2 symmetric stretching and the 1400 cm À 1 band is assigned to the CH 2 wagging vibration [33,34]. The position of the absorption bands does not exhibit noticeable change in graphene-P(VDFTrFE) film.…”
Section: Resultsmentioning
confidence: 98%
“…To improve the conductivity, PANI/GO was re‐doped with 1 M HCl as a dopant, and the conductivity obtained at room temperature was 0.058 S/m. Beova et al and Zhang et al reported the synthesis of PANI/GN nanocomposites via the in situ polymerization of aniline. The electrical conductivity reported by Beova et al was 37 S/m, whereas Zhang et al reported the electrical conductivity for PANI/GN (10, 50, and 100 wt%) to be 168.7, 22.8, and 143 S/m, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This challenge is solved by introduction of acidic groups in the side chains of the polymer (self-doped polyaniline; Jaymand, 2013 ) or by the addition of high-molecular anionic substances (Zhang et al, 2008 ). The reversibility of the polyaniline potential can be improved by implementation of conductive materials, i.e., carbon nanotubes (Bavastrello et al, 2004 ), graphene (Jaworska et al, 2012 ; Boeva et al, 2014 ), or noble metal nanoparticles (Shiigi et al, 2012 ; Lorestani et al, 2015 ).…”
Section: Polyaniline In the Assembly Of Potentiometric Sensorsmentioning
confidence: 99%